2015
DOI: 10.1039/c5ob00796h
|View full text |Cite|
|
Sign up to set email alerts
|

Selective photoregulation of the activity of glycogen synthase and glycogen phosphorylase, two key enzymes in glycogen metabolism

Abstract: Glycogen is a polymer of α-1,4- and α-1,6-linked glucose units that provides a readily available source of energy in living organisms. Glycogen synthase (GS) and glycogen phosphorylase (GP) are the two enzymes that control, respectively, the synthesis and degradation of this polysaccharide and constitute adequate pharmacological targets to modulate cellular glycogen levels, by means of inhibition of their catalytic activity. Here we report on the synthesis and biological evaluation of a selective inhibitor tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…1, was tested against purified preparations of commercially available RMGP a and recombinantly produced Ec GS and SuSy4. 16 First, to establish the optimal conditions of the assay, the kinetic parameters K m and V max of the three enzymes for their respective substrates were determined: RMGP a activity was measured in the direction of glycogen phosphorolysis and Ec GS and SuSy4 in the direction of synthesis of glycogen and sucrose, respectively (Fig. S-1 and Table S-2, ESI † ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1, was tested against purified preparations of commercially available RMGP a and recombinantly produced Ec GS and SuSy4. 16 First, to establish the optimal conditions of the assay, the kinetic parameters K m and V max of the three enzymes for their respective substrates were determined: RMGP a activity was measured in the direction of glycogen phosphorolysis and Ec GS and SuSy4 in the direction of synthesis of glycogen and sucrose, respectively (Fig. S-1 and Table S-2, ESI † ).…”
Section: Resultsmentioning
confidence: 99%
“…12 The synthesis of molecules with new inhibitory profiles in terms of potency and/or selectivity is of special interest in the case of GTs, since there are few known inhibitors. 1316 …”
Section: Introductionmentioning
confidence: 99%
“…In 2015, Diaz-Lobo et al [ 21 ] reported on the synthesis and biological evaluation of O -glycoside—a selective inhibitor that consists of an azobenzene moiety glycosidically linked to the anomeric carbon of a glucose molecule. The molecule incorporates an azobenzene photoswitch whose conformation can be significantly altered by irradiation with UV light.…”
Section: O -Glycosides As Antidiabetic Agentsmentioning
confidence: 99%
“…Although compound 9 was synthesized as a 1:4 mixture of the α- and β-anomers, analysis suggested that the more abundant β-anomer is the one responsible for the observed inhibition. So, Diaz-Lobo et al showed that the ability to selectively photocontrol the catalytic activity of key enzymes of glycogen metabolism might represent a new approach for the treatment of glycogen metabolism disorders [ 21 ].
Scheme 1 Synthesis of 4-(phenylazo)phenyl- d -glucopyranoside 9 [ 21 ]
…”
Section: O -Glycosides As Antidiabetic Agentsmentioning
confidence: 99%
“…Photochromism has attracted increasing interest of carbohydrate community to develop photoswitchable glycoconjugates for light‐controlled carbohydrate‐lectin interactions, intracellular target recognition, cell adhesion, chiral discrimination, photoregulation of enzyme activity and protein conformation, or as photoresponsive surfactants, hydrogelators, organogelators, liquid crystals, as well as water‐compatible molecular logic gate. Azobenzene,, spiropyran, and diarylethene have been used as photochromic moiety in these glycoconjugates, with the azobenzene being the most employed one, probably due to its small size, its excellent photostability and the large changes in molecular size, conformation and dipole moment between E and Z isomers.…”
Section: Introductionmentioning
confidence: 99%